Some Celebrity Theorems of the Mulatu Numbers - Mulatu, Lemma,; Mohammed, Mustafa; Lambright, Jonathan (IJRDO -JOURNAL OF MATHEMATICS, 2019)
The Mulatu numbers are sequences of numbers of the form 4, 1, 5, 6, 11, 17, 28, 45, ….  The numbers have wonderful and amazing properties and patterns. In mathematical terms, it is defined by the following recurrence relation: Mn The first number of the sequence is 4, the second number is 1, and each subsequent number is equal to the sum of the previous two numbers of the sequence itself. That is, after two starting values, each number is the sum of the two preceding numbers. In this paper, we investigate the effect of the Core Theorem given below in providing different new proofs  for  some  important results  which are already  known.